Labor Migration from Nepal and Household Livelihoods: Drivers, Outcomes, and Policy Implications - Kafle, Jeeb Narayan; Mahat, Kushendra Bahadur (Journal of Advanced Academic Research, 2026)
This mixed-methods study examines labor migration from Nepal and its effects on household livelihoods, focusing on drivers, remittance allocation, and implications for livelihood diversification and rural sustainability. Quantitative analysis includes descriptive statistics, bivariate comparisons, and multivariate regression models with robustness checks (propensity score matching and clustered standard errors). Qualitative thematic analysis explains decision making, gendered dynamics, and institutional constraints. Key findings indicate that smaller landholdings, limited local employment, and lower educational attainment increase migration likelihood; remittances raise short-term consumption but have mixed effects on productive investment and long-term diversification. Policy recommendation emphasizes targeted skills training, financial inclusion for remittance recipients, and community level programs to translate remittances into sustainable local investments.